PEMODELAN TERMODINAMIKA STEAM REFORMER UNTUK PRODUKSI GAS H2 MENGGUNAKAN GAS ALTERNATIF HASIL PEMBAKARAN COKES - Wikanta, Deddy Kurniawan (METANA, 2009)
Abstract Most of H2 gas industry produce its product from natural gas by reforming. Availability of natural gas stay no longer. One of alternative substitute gas is flue gas from cokes. The problem is how to model thermodynamically the reformer so that it operates as same in order compare with using natural gas. For this reason it needs to be simulated thermodynamic model to know the process tendency to succeed. This research is done in 2 step, namely : thermodynamic modelling and simulation. The result give recommendation that flue gas from cokes can be used as gas substitute to feed reformer. Keywords : reformer; thermodynamic